The practicality of the 7e learning cycle LKS model with a scientific approach to facilitate students’ mathematical connection abilities - azizah, Azizah; D, Zuhri; Maimunah, Maimunah (Desimal: Jurnal Matematika, 2021)
This study aims to describe the practicality of the 7e learning cycle LKS model with a scientific approach to facilitate students' mathematical connection abilities. The research and development with the ADDIE model consist of the stages of analysis, design, development, implementation and evaluation. The practicality test of the LKS was carried out for small group trials of 9 students at the implementation stage. The method used is descriptive statistics to get the average value and percentage. Learning tools are said to be practical if their minimum level of practicality is practical. Based on the analysis of the results of student response questionnaires, the average percentage of student response questionnaires was 91.59% and was categorized as very practical. This means that this LKS is easy to use and useful for students.